Determination of Microinsurance Premiums in Cattle Farms Based on Protein Content Index and Milk Production Using the Black-Scholes Method - Rahadi, Fabiyan; Susanti, Dwi; Halim, Nurfadhlina Binti Abdul (Indonesian Operations Research Association (IORA), 2023)
Micro insurance is an insurance product that is intended for low-income people with features and administration that are simple, easy to obtain, economical prices and immediate settlement of compensation. Cattle business insurance is an effort to protect breeders in event of a risk of death and loss of cattle, this insurance product is a protection against worries the burden of a large premium. This study aims to calculate the premium price using the Black-Scholes method. In this study, a correlation analysis was conducted to determine the influence the protein content on cowâ€™s milk production. Then, modelling the protein content using ARIMA-GARCH and determining the premium using the Black-Scholes method. The results showed that the protein content of milk in cowâ€™s milk production has a positive correlation. Protein content follows the ARIMA(1,0,0)-GARCH(1) model. Based on the results of the analysis it can be concluded that the bigger protein content in milk, the higher premium that needs to paid.Â